2023
DOI: 10.3389/fpls.2023.1088849
|View full text |Cite
|
Sign up to set email alerts
|

Grass-legume mixture and nitrogen application improve yield, quality, and water and nitrogen utilization efficiency of grazed pastures in the loess plateau

Abstract: Grazing on cultivated grassland is a green agricultural model. However, in China's Loess Plateau, the type of cultivated grassland suitable for grazing and the amount of nitrogen application is still unclear, which has led to the failure of this model to be widely implemented. In this context, we set up an experiment using three grass planting types, including monoculture of alfalfa (Medicago sativa L.), monoculture of brome (Bromus inermis L.), and mixed planting of the two forages. Under each planting type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…Importantly, mixed perennial crops had the greatest effects in enhancing the soil multifunctionality and C cycle multifunctionality by significantly augmenting soil C input and EEAs. These findings were also consistent with previous research, indicating that it should be "compared with the perennial grass, legume, and their mixture not only yields a greater quantity of matter (not significant) but also provide higher energy output [51]. However, the selection of mixed perennial crops should consider not only the complementary effects but also the potential for interspecific competition.…”
Section: Implications and Uncertaintiessupporting
confidence: 91%
“…Importantly, mixed perennial crops had the greatest effects in enhancing the soil multifunctionality and C cycle multifunctionality by significantly augmenting soil C input and EEAs. These findings were also consistent with previous research, indicating that it should be "compared with the perennial grass, legume, and their mixture not only yields a greater quantity of matter (not significant) but also provide higher energy output [51]. However, the selection of mixed perennial crops should consider not only the complementary effects but also the potential for interspecific competition.…”
Section: Implications and Uncertaintiessupporting
confidence: 91%
“…This may be due to the fact that appropriate deficit irrigation and N supply is conducive to improving plant water and fertilizer use efficiency, promoting root development and canopy growth, and thus increasing alfalfa CWP and yield ( Al-Gaadi et al., 2017 ; May et al., 2022 ). However, too low and too high N application rate affect the water uptake and utilization, and then reduce the water use efficiency ( Xu et al., 2023 ). This study results showed that under the same irrigation level, there was a negative correlation between NUE, PEPN, and N rate, and the PEPN value under moderate irrigation level (W2) was significantly higher than that under low irrigation level (W1).…”
Section: Discussionmentioning
confidence: 99%